(x-16)-(2x-13)=1

Simple and best practice solution for (x-16)-(2x-13)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-16)-(2x-13)=1 equation:


Simplifying
(x + -16) + -1(2x + -13) = 1

Reorder the terms:
(-16 + x) + -1(2x + -13) = 1

Remove parenthesis around (-16 + x)
-16 + x + -1(2x + -13) = 1

Reorder the terms:
-16 + x + -1(-13 + 2x) = 1
-16 + x + (-13 * -1 + 2x * -1) = 1
-16 + x + (13 + -2x) = 1

Reorder the terms:
-16 + 13 + x + -2x = 1

Combine like terms: -16 + 13 = -3
-3 + x + -2x = 1

Combine like terms: x + -2x = -1x
-3 + -1x = 1

Solving
-3 + -1x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -1x = 1 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = 1 + 3
-1x = 1 + 3

Combine like terms: 1 + 3 = 4
-1x = 4

Divide each side by '-1'.
x = -4

Simplifying
x = -4

See similar equations:

| 5y-12x=-3 | | 8x-2=y | | (3c-4c^2+c^3)-(5c^2+8c^3-6c)= | | (-4m^2+m-10)+(3m+12-7m^2)= | | 5+3x=3+5x | | 8w-5=35-12w | | x-2x=200 | | (9a^2-4-5a)-(12a-6a^2+3)= | | x-2x=300 | | (3+5i)-(4-6i)= | | -17=6x-(1+2x) | | 3k^5+4k^2-6k^5-5k^2= | | X-2=5-x | | 3xy-7x(5y-4m)= | | 4b+7a=10 | | -4x^4+x^2-10+12x^4-7x^2= | | 16z-11+2z+1=-1 | | 4-5v-12v-6v^2-4-2v^3= | | 7x^2+22x-2=0 | | y^2+2y+5-3y^2-5y= | | 7x^2+23x-8=0 | | 2y-5y+8y=30 | | 5x^2+18x-4=0 | | 15x-5=7x+7 | | 7x^2+12x-7=0 | | X-2.5=-7.1 | | 104-6x=30x+24 | | 8x+5y-3x+y=0 | | 8x-26=4x+54 | | F(-4)=-x^2-2x | | 3x-4+3x=14 | | 5w+(-16)=-76 |

Equations solver categories